P=(1+ $\frac{√a}{a+1}$ ):( $\frac{1}{√a-1}$ – $\frac{2√a}{a√a+√a-a-1}$) rút gọn biểu thức ạ

P=(1+ $\frac{√a}{a+1}$ ):( $\frac{1}{√a-1}$ – $\frac{2√a}{a√a+√a-a-1}$) rút gọn biểu thức ạ

0 thoughts on “P=(1+ $\frac{√a}{a+1}$ ):( $\frac{1}{√a-1}$ – $\frac{2√a}{a√a+√a-a-1}$) rút gọn biểu thức ạ”

  1. Đáp án:

    \(\dfrac{{a + \sqrt a  + 1}}{{\sqrt a  – 1}}\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    DK:a \ge 0;a \ne 1\\
    P = \left( {\dfrac{{a + 1 + \sqrt a }}{{a + 1}}} \right):\left[ {\dfrac{1}{{\sqrt a  – 1}} – \dfrac{{2\sqrt a }}{{\left( {\sqrt a  – 1} \right)\left( {a + 1} \right)}}} \right]\\
     = \dfrac{{a + \sqrt a  + 1}}{{a + 1}}:\left[ {\dfrac{{a + 1 – 2\sqrt a }}{{\left( {\sqrt a  – 1} \right)\left( {a + 1} \right)}}} \right]\\
     = \dfrac{{a + \sqrt a  + 1}}{{a + 1}}.\dfrac{{\left( {\sqrt a  – 1} \right)\left( {a + 1} \right)}}{{{{\left( {\sqrt a  – 1} \right)}^2}}}\\
     = \dfrac{{a + \sqrt a  + 1}}{{\sqrt a  – 1}}
    \end{array}\)

    Reply

Leave a Comment